The Soft Skills of Millenial Generation Orientee Nurses - Ernawati, Ernawati; Bratajaya, Cicilia Nony (Jurnal Keperawatan, 2020)
Introduction: In doing their work, nurses often deal with other nurses, other health workers, patients, and patients' families. In addition, the job as a nurse in a hospital is related to the ability to be able to work together in teams. Therefore, a nurse is expected to have soft-skill attributes which, in this Millennial era, have different challenges from the previous era. Objective: The purpose of this study is to include soft-skills inherent in self-care nurses who have just connected the workforce from the point of view of senior nurses associated with them in the hospital. Method: Qualitative research involving 7 informants, namely senior nurses in the hospital, the informants were selected by purposive sampling based on inclusion criteria. Results: The results raised the theme of millennial nurses' soft-skills which are grouped into 3 groups of soft-skills, namely: (1) personal skills (personal skills), (2) social skills (social skills), (3) methodological skills (methodological skills), and the theme of soft-skill internalization. Discussion: Can reduce soft skills still need to be internalized for students since the time of education.